2017/3 Sayılı motorlu taşıtlar sektöründeki dikey anlaşmalara ilişkin grup muafiyet tebliği incelemesi - Alkan, Ayça Güntülü (İstanbul Bilgi Üniversitesi, 2018)
[Abstract Not Available]
The examination of motor vehicles sector vertical agreements block exemption communique numbered 2017/3